MODERN VIEWS ON TOOTH WHITENING - O.S. Kyrmanov; A.V. Lemeshko (Український стоматологічний альманах, 2020)
Resume. In the modern world, the appearance of teeth is of great importance. Beautiful white teeth are not only a sign of good health, but also an element of culture and well-being.